Similarities and differences in the clinical features and management of primary lymphedema and kaposiform hemangioendothelioma associated with lymphedema in children - Zhang, Yujia; Qiu, Tong; Yang, Congxia; Zhou, Jiangyuan; Yang, Min; Gong, Xue; Zhang, Zixin; Lan, Yuru; Zhang, Xuepeng; Chen, Siyuan; Ji, Yi (Frontiers in Pediatrics, 2025)
BackgroundPrimary lymphedema (PLE) and kaposiform hemangioendothelioma-related lymphedema (KLE) are rare vascular anomalies (VAs). This study aimed to examine the clinical features, management, and prognosis of PLE and KLE.MethodThe clinical features, imaging, treatments, and outcomes of 12 patients with PLE and 12 patients with KLE were retrospectively reviewed.ResultsThe mean age at which signs/symptoms were diagnosed was 68.2 months for PLE patients and 25 months for KLE patients. In PLE, the involvement of multiple sites is common, whereas in KLE, it typically affects a single site. Morbid obesity, which is common in adult patients, is rare in pediatric PLE and KLE patients. Imaging agent accumulation was observed in KLE but not in PLE via lymphoscintigraphy. In contrast, complications of PLE primarily involve skin and soft tissue, whereas musculoskeletal system complications are more common in KLE. Regarding prognosis, most patients stabilize or even experience lesion regression after standard treatment.ConclusionPLE and KLE share clinical symptoms. PLE often involves multiple sites, whereas KLE typically presents unilaterally with local lymphatic stasis. Standardized treatment enables the majority of children with lymphedema to control the disease without progression, with KLE showing potential reversibility. Given their rarity, a multidisciplinary approach is crucial for diagnosis and management.